PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA PERUSAHAAN PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA PEKALONGAN - Prastika, Nurhikmah Esti; Purnomo, Djauhar Edi (JURNAL LITBANG KOTA PEKALONGAN, 2014)
Micro, Small, Medium Enterprises (MSMEs) is the enterpises a business has to control by group society or families. Micro, Small, Medium Enterprises (MSMEs) SMEs has a strategic role in national economic development, because in addition to contributing to national economic growth also can provide the employees in large numbers. Inability to provide accounting and used information is one of the weakness of the side of management. This study focus on influence accounting information system toward performance in a company Micro, Small, Medium Enterprises (MSMEs). Performance of the firms is a condition of the companies that were analyzed with the tools of financial analysis so it can be good and bad condition that reflect the firms financial performance in a particular period. The population in tihis study is owners Micro, Small, Medium Enterprises which are distribute 1.201 unit the city of Pekalongan. The sample of this was 100 respondent owners in Micro, Small, Medium Enterprises (MSMEs). The sample using convinience sampling technics, convenience sample is formed when we select elements from a population on the basis of what elements are easy to obtain with owners Micro, Small, Medium Enterprises (MSMEs). The analytical tool used in this study is multiple linear regression. The result of this study indicated a variable accounting information system affect on variable performance Micro, Small, Medium Enterprises (MSMEs) in Pekalongan city area. Keywords : Micro, Small, Medium Enterprises (MSMEs), accounting information system,performance